IMPLEMENTASI KERANGKA KUALIFIKASI NASIONAL INDONESIA DI LEMBAGA KURSUS UNIVERSAL SKILL PEKANBARU - Risma B; Azhar Azhar; Makhdalena Makhdalena (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2018)
This research is described the implementation of National QualificationFramework at Universal Skill Course in Pekanbaru about the curriculum concept and theregistration of new students process, educational processes, competence exams until the receivesof the certificates. This research used the qualitative approach, the data of research got by theleader of Universal Skill course, tutor, admission, and students. The data collectives got bytriangulation technique through observation, interviews, and documentations research. The reportof the research shows some indicators, they are 1) the new students’ registration processes atlevel 2 of Accountant Junior Technician Assistance is in roles of NQF that is the students haveto graduate of Senior High School level. 2) The Education processes at Universal Skill hasused SKKNI thus suitable with KKNI curriculum, besides Universal Skill has got theAccreditation of BAN PNF with score “B”, it shows that implementation of KKNI at UniversalSkill is very good. 3) The students’ study achievement at Universal Skill are 100%, it measuredby the SKL achievement has match as the SKKNI procedure. The SKL achievement provedby the students’ score reports on certificate around 80 – 90. 4) The influence of successfulfactors in implementing of KKNI at level 2 of Accountant Junior Technician Assistance asfollows; The curriculum which is used refers to the SKKNI thus the output of the courseproduce the workers whom ready to work and compete in business world; the other factor isthe tutor recruited from practitioners in his/ her own fields so that in learning processes thetutors discuss about some cases which are influences the successful of implementation ofKKNI at Universal Skill course is the certificates of Universal Skill prints in English languageso that comes the advantages to compete with the foreigner and also in next MEA. Meanwhiles the barrier factors of the implementation of KKNI at Universal Skill is the late ofdistribute the certificates from the government.